Analiza ryzyka ubezpieczeniowego w wybranych rodzajach ubezpieczeń finansowych - Kowalczyk, Patrycja (Analysis of insurance risk in the selected types of financial insurance, 2006)
In recent years the financial insurance has been of more and more importance on the Polish market. The number of products within the scope of financial insurance offered by insurance companies conducting business activity in branch II is increasing. This increasing range of financial insurance products is caused not only by the development of the real estate market affecting also the development of products offered by banks, but also first of all by the increasing awareness of business entities, which look for different forms of protection against a broadly defined financial risk. Analysis of insurance risk in the financial insurance is very complex and differs from the analogous risk analysis made for other groups of property insurance. The aim of this study is to present the specificity of financial insurance from the point of view of insurance risk taking into special consideration the insurance of bank credit.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 206-214